Exploring the Factors Influencing Road Accidents in Parit Raja: An In-Depth Research Investigation - Gilie, Jacqualine Cheah Rigi; Ismail, Shafawi (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Malaysia consistently grapples with a high frequency of traffic accidents that result in significant bodily harm, property damage, and loss of life. Despite the government’s implementation of various measures to mitigate road accidents, they persist across the country. Notably, Johor has emerged as one of the top two regions with a high incidence of accidents in Malaysia. Alarmingly, over half of fatal accidents on rural roads involve federal infrastructure, and more than a quarter occur on state highways. This case study focuses on evaluating the road accident statistics in the town of Parit Raja, Johor. The aim of this study is to identify the specific causes behind the road accidents in this locality. The research employed SPSS software for data analysis to generate descriptive statistics related to the demographic characteristics of the respondents and to investigate the correlation among four factors influencing road accidents. The results of the ANOVA analysis revealed no significant differences (at p = 0.05) for a sample size of 50 regarding demographic factors such as Age Category, Gender Category, Marital Status, and Education Background in their perception of factors influencing road accidents. Additionally, Pearson Correlations analysis indicated a robust statistical correlation (r > 0.5, n = 50, p < 0.05) among Human factors, Road Conditions, Weather Conditions, and Poor Car Maintenance. To address these findings, proposed intervention plans include the maintenance of damaged roads, the installation of Automated Enforcement Systems (AES), and the implementation of awareness programs promoting safe driving practices. These initiatives aim to significantly reduce road accident cases in Parit Raja.